(ii) Starting from (– 6) × 3, find (– 6) × (–7)

Answers (1)

Given,

(- 6) \times 3 = -18

\\ (-6) \times 2 = -12 = -18 +6 \\ (-6) \times 1 = -6 = -18+12 \\ (-6) \times 0 = 0 = -18 + 18 \\ (-6) \times (-1) = 6 = -18+24 \\ (-6) \times (-2) = 12 = -18+30 \\ \\ (-6) \times (-3) = 18 = -18+36

Therefore,

\\ (-6) \times (-7) = -18+60=42

Preparation Products

JEE Main Rank Booster 2021

This course will help student to be better prepared and study in the right direction for JEE Main..

₹ 13999/- ₹ 9999/-
Buy Now
Rank Booster NEET 2021

This course will help student to be better prepared and study in the right direction for NEET..

₹ 13999/- ₹ 9999/-
Buy Now
Knockout JEE Main April 2021 (Subscription)

An exhaustive E-learning program for the complete preparation of JEE Main..

₹ 4999/-
Buy Now
Knockout NEET May 2021

An exhaustive E-learning program for the complete preparation of NEET..

₹ 22999/- ₹ 14999/-
Buy Now
Knockout NEET May 2022

An exhaustive E-learning program for the complete preparation of NEET..

₹ 34999/- ₹ 24999/-
Buy Now
Exams
Articles
Questions